A New Methodology to Assess Indirect Losses in Bridges Subjected to Multiple Hazards - Davide Forcellini (Emerging Science Journal, 2018)
Decision making approaches to manage bridge recovering after the impact of multiple hazards are increasing all over the world. In particular, bridges can be considered critical links in highway networks because of their vulnerability and their resilience can be assessed on the basis of evaluation of direct and indirect losses. This paper aims at proposing a new methodology to assess indirect losses for bridges subjected to multiple hazards. The method applied to calculate direct costs is the credited Performance Based Earthquake Engineering (PBEE) methodology by the Pacific Earthquake Engineering Research (PEER) center. Therefore, the main objective of the study consists in the assessment of indirect losses that are generally neglected elsewhere. In particular, the paper proposes to calculate indirect losses from direct costs and to divide them into connectivity losses and prolongation of time. The presented formulation has been applied to a real case study aimed at strengthening a benchmark bridge with several isolated configurations. The results show that the application of the proposed methodology allows to evaluate possible solutions to strengthen the original configuration.